2011
DOI: 10.5840/beq20112113
|View full text |Cite
|
Sign up to set email alerts
|

Where Is the Accountability in International Accountability Standards?: A Decoupling Perspective

Abstract: ABSTRACT:A common complaint by academics and practitioners is that the application of international accountability standards (IAS) does not lead to significant improvements in an organization’s social responsibility. When organizations espouse their commitment to IAS but do not put forth the effort necessary to operationally enact that commitment, a “credibility cover” is created that perpetuates business as usual. In other words, the legitimacy that organizations gain by formally adopting the standards may sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
161
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(167 citation statements)
references
References 68 publications
4
161
0
2
Order By: Relevance
“…In their view, low-entry barriers for adopting a CR standard and lax enforcement mechanisms and reporting requirements after adoption encourage shirking (King & Lenox, 2000). Consequently, researchers have started paying attention to whether organizations actually implement CR standards (Aravind & Christmann, 2011;Boiral, 2007) and examining the various antecedents and consequences of decoupling (Behnam & MacLean, 2011;Christmann & Taylor, 2006). Such research has found that CR standardization initiatives are often implemented superficially to produce a 'green' and socially responsible image that does not affect organizational core activities.…”
Section: Standardization-as-entrenchmentmentioning
confidence: 99%
“…In their view, low-entry barriers for adopting a CR standard and lax enforcement mechanisms and reporting requirements after adoption encourage shirking (King & Lenox, 2000). Consequently, researchers have started paying attention to whether organizations actually implement CR standards (Aravind & Christmann, 2011;Boiral, 2007) and examining the various antecedents and consequences of decoupling (Behnam & MacLean, 2011;Christmann & Taylor, 2006). Such research has found that CR standardization initiatives are often implemented superficially to produce a 'green' and socially responsible image that does not affect organizational core activities.…”
Section: Standardization-as-entrenchmentmentioning
confidence: 99%
“…Our paper's contribution is twofold. First, our study prompts the rethinking of decoupling and "greenwash" as detrimental to the institutionalization of CR as a global governance mechanism, as currently conceived in the mainstream CR literature (Aravind & Christmann, 2011;Behnam & MacLean, 2011;Delmas & Montes-Sancho, 2011). Second, we integrate institutional theory (Scott, 2008) and the path dependence concept (Sydow et al, 2009;Vergne & Durand, 2010) by adopting an explicit proccessual perspective which allows to temporally separate theoretical incompatibilities among transparentists and opacitists (see Okhuysen & Bonardi, 2011;Poole and van de Ven, 1989).…”
Section: /37mentioning
confidence: 88%
“…On the one hand, it allows for higher degrees of contextualization and flexibility, as the complier usually makes the final decision about how to fit the rules of the standard into the particular organizational context (Ahrne and Brunsson 2011). On the other hand, this flexibility can also be misused leading to accusations of standard adopters not walking their talk (Behnam and MacLean 2011).…”
Section: Csr Standardsmentioning
confidence: 99%